Inflasi dan krisis ekonomi: Konsep dasar, faktor penyebab, upaya mengatasi - Salsabilla, Marsha; Azhar, M. Syafiul (Maliki Interdisciplinary Journal, 2024)
This article discusses inflation and the economic crisis. This research is demonstrated in knowing the basic concepts, causal factors, and efforts to overcome inflation and the economic crisis. The economic crisis and inflation are two main problems that repeatedly occur in countries around the world, including Indonesia. Economic crises occur due to various causes, such as inefficient government procedures, the global financial crisis, and so on. The impact of the economic crisis is very burdensome on society, such as unemployment, poverty and shrinking purchasing power. In addition, inflation begins with the prices of goods and services increasing significantly in a short period of time. Inflation can affect people’s daily lives, such as reducing purchasing power and increasing the cost of living. Inflation itself can be controlled in several ways, such as tightening monetary policy, controlling salaries, increasing investment, tightening fiscal policy, and so on.